Influencia de las lianas, forma e iluminación de copa en el crecimiento y CO2e del bosque varillal, Iquitos-Perú, 2005-2018 - Torres Vargas, Rosula Corina (2021)
We carry out the study with the objective of determining the influence of the vines, shape and tree canopy position on the growth and CO2e of the high dry varillal forest, using three permanent sampling plots. In the 2005-2007 intercensal period, the average annual increase (AAI) in the DAP was 0,88 ± 0,99 cm/year; 0,0034 ± 0,0048 m2/year in basal area of the tree and 0.0462 ± 0.0703 m3 /year in volume. In the 2007-2018 period, the DBA AAi was 0,503 ± 0,473 cm / year, at basal area of the tree was 0,0024 ± 0,0032 m2 / year and in volume 0,0305 ± 0,0430 m3 / year. Between diametric class the 10, 20, 30, 40, 50, 60 and 70 cm, the AAI was 0,41 ± 0,25; 0,89 ± 0,66; 1,24 ± 1,50; 1,53 ± 1,28; 1,68 ± 1,90; 1,49 ± 1,33 and 0,38 ± 0,30 cm / year. In basal area of the tree was 0,0004 ± 0,0003; 0,0013 ± 0,0006; 0,0036 ± 0,0020; 0,0061 ± 0,0027; 0,0081 ± 0,0031; 0,0095 ± 0,0067 and 0,0088 ± 0.0088 m2 / year; in volume it was 0,009 ± 0,0038; 0,031 ± 0,015; 0,06 ± 0,05; 0,11 ± 0,09; 0,15 ± 0,0118; 0,19 ± 0,19 and 0,12 ± 0,09 m3 / year respectively in the 2005-2007 period. In the period 2007 - 2018 the AAI was 0,19 ± 0,10; 0,38 ± 0,19; 0,82 ± 0,52; 1,05 ± 0,51; 1,12 ± 0,50; 1,22 ± 0,96; 0,88 ± 0,90 cm / year; at basal area of the tree was 0,0004 ± 0,0003; 0,0013 ± 0,0006; 0,0036 ± 0,0020; 0,0061 ± 0,0027; 0,0081 ± 0,0031; 0,0095 ± 0,0067 and 0.0088 ± 0.0088 m2 / year. In volume, it was 0.0046 ± 0.0025; 0.0152 ± 0.0059; 0.0413 ± 0.0179; 0,0814 ± 0,0372; 0,1074 ± 0,0340; 0,1384 ± 0,082 and 0,1309 ± 0,0867 m3 /year respectively. Tree growth in DBA, basal area and volume varied between categories of vines in the two intercensal periods (p <0,01). It also varied between tree canopy position categories (p <0,001); and between cup-shaped categories (complete, irregular, incomplete) (p <0,02).